Aisyiyah muballighat’s digital da’wah on YouTube: expanding pious agency, identifying challenges, and mapping emerging trends - Dewi, Kurniawati Hastuti; Annisa, Firly; Alamsyah , Purnama (Indonesian Journal of Islam and Muslim Societies, 2026)
Situated within the context of Society 5.0 and the rise of the Internet of Things (IoT), this paper examines how ‘Aisyiyah’s Muballighat (female preachers of Muhammadiyah) engage in digital da’wah, particularly through YouTube, focusing on their strategies, challenges, and emerging trends. This qualitative research draws on interviews and Focus Group Discussions with ‘Aisyiyah Muballighat and members of the Majelis Tabligh and Ketarjihan (MTK) central board of ‘Aisyiyah, alongside an observational analysis of their YouTube content from 2020 to 2025. The findings indicate that while the MTK central board of ‘Aisyiyah initially relied on the Muhammadiyah Majelis Tabligh YouTube channel during 2020–2022, they have, since 2023, successfully established and managed their own channel. This digital expansion highlights how ‘Aisyiyah’s Muballighat are actively shaping gendered religious authority and asserting their presence within digital spaces that male religious figures have traditionally dominated. Nevertheless, challenges remain, including limited financial support, rigid SOPs, weak personal branding, and low audience engagement. This paper further reveals that the YouTube content produced by the MTK central board of ‘Aisyiyah in 2023–2025 not only centers on themes of faith and piety in the Risalah Perempuan Berkemajuan, reflecting forms of “pious agency”, but also demonstrates a growing engagement with contemporary issues. This shift indicates an expansion of this “pious agency” into a broader form of public piety, where religious commitment is articulated through social responsibility and active civic participation Dalam konteks Masyarakat 5.0 dan munculnya Internet of Things (IoT), makalah ini mengkaji bagaimana Muballighat ‘Aisyiyah (pendakwah perempuan Muhammadiyah) terlibat dalam dakwah digital, khususnya melalui YouTube, dengan fokus pada strategi, tantangan, dan tren yang muncul. Penelitian kualitatif ini didasarkan pada wawancara dan Focus Group Discussions dengan Muballighat ‘Aisyiyah dan anggota dewan pusat Majelis Tabligh dan Ketarjihan (MTK) ‘Aisyiyah, serta analisis observasional terhadap konten YouTube mereka dari tahun 2020–2025. Temuan menunjukkan bahwa meskipun dewan pusat MTK ‘Aisyiyah awalnya bergantung pada saluran YouTube Majelis Tabligh Muhammadiyah selama tahun 2020–2022, sejak tahun 2023 mereka telah berhasil membangun dan mengelola saluran mereka sendiri. Ekspansi digital ini menyoroti bagaimana Muballighat ‘Aisyiyah secara aktif membentuk otoritas keagamaan berbasis gender dan menegaskan kehadiran mereka di ruang digital yang secara tradisional didominasi oleh tokoh agama laki- laki. Meskipun demikian, tantangan tetap ada, termasuk dukungan keuangan yang terbatas, SOP yang kaku, personal branding yang lemah, serta keterlibatan audiens yang rendah. Penelitian ini lebih lanjut mengungkapkan bahwa konten YouTube yang diproduksi oleh dewan pusat MTK ‘Aisyiyah pada tahun 2023–2025 tidak hanya berpusat pada tema iman dan kesalehan dalam Risalah Perempuan Berkemajuan, yang mencerminkan bentuk-bentuk “aksi kesalehan”, tetapi juga menunjukkan keterlibatan yang semakin meningkat dalam isu-isu kontemporer. Pergeseran ini menunjukkan perluasan aksi kesalehan ke dalam bentuk kesalehan publik yang lebih luas, di mana komitmen keagamaan diartikulasikan melalui tanggung jawab sosial dan partisipasi sipil yang aktif.